Differences in mature human milk metabolic profiles based on delivery mode and parity - Tang, Jiayue; Shen, Cai; Yao, Dan; Yu, Jingwen; Liu, Yanan; Tu, Maolin; Zhang, Hong; Xu, Xuebing; Lai, Oi Ming; Cheong, Ling Zhi (Elsevier, 2025)
Human milk (HM) is regarded as the gold standard for infant nutrition. The metabolite profiles of mature human milk (MHM) have been reported to be affected by maternal physiological conditions, lactation stage, and maternal diets. We collected MHM (3–6 months postpartum) from 32 healthy mothers with different parities and delivery modes. Then, GC-MS and LC-MS were used to perform an untargeted metabolomic study. A clear distinction can be observed in terms of MHM metabolites of mothers with different delivery modes and parities with a 95% confidence interval. A total of 119 differentially expressed metabolites (DEMs) were identified in MHM of women with different delivery modes. Metabolic pathway analyses indicated that these DEMs were mainly associated with fatty acid biosynthesis. The higher abundances of these DEMs in MHM of cesarean women may be due to the differing levels of cortisol and oxytocin between mothers with different delivery modes. Meanwhile, 284 DEMs were identified in MHM of women with different parities. These DEMs were primarily related to ABC transporters, center carbon metabolism in cancer, and D-amino acid metabolism. These findings highlighted the impact of delivery mode and parity on HM metabolite composition. Further research is needed to explore the long-term health implications of these metabolic differences and optimize infant nutrition strategies.